Studi Komparasi Hasil Belajar Siswa antara LKS Kharisma dengan LKS PAIKEM pada Materi Sistem Peredaran Darah Manusia - Wa Diati Buton; Cornelia Pary; M Yani Kamsurya; Rizal Kamsurya; Lastri Lastri (Lembaga Intelektual Muda (LIM) Maluku, 2022)
Student learning outcomes should be the main focal point in learning. Good learning outcomes show the level of students' understanding of the teaching material, as well as the success of teachers in carrying out learning in the classroom. The study aims to determine the differences in student learning outcomes taught using LKS Kharisma and LKS PAIKEM on the material of the human circulatory system. The type of research used is quantitative, namely a comparative study or comparative study with a total sample of 38 people. The sample was selected using the cluster random sampling technique. The instruments used are tests and observations. Tests are carried out to determine student learning outcomes and observation is used to objectively determine learning conditions. The data analysis technique used is to use the t-test. The results of the analysis showed that there were differences in student learning outcomes taught using LKS Kharisma and LKS PAIKEM on the material of the human circulatory system. The average score of students who studied using LKS PAIKEM was 73.84 and students who studied with LKS Kharisma obtained an average score of 64.74